Real Exchange Rate and Economic Growth in China - Hua, Ping (Journal of Reviews on Global Economics, 2012)
Abstract: By proposing a real exchange rate augmented Cobb-Douglas production function, it is demonstrated that the real exchange rate exerts multiple effects on economic growth. If a real appreciation has negative effects on growth by deteriorating international competitiveness in the tradable sector and by causing job losses, at the same time it exercises positive effects on economic growth by favoring capital intensity, human capital and by exerting pressure for efficiency improvements. The function is estimated by using the GMM system estimation approach and a panel data for the 29 Chinese provinces over the period from 1987 to 2008. The results show that the real exchange rate appreciation had a negative effect on economic growth, which was more marked in coastal provinces than in inland provinces, contributing to a reduction in the difference in GDP per capita between the two kinds of provinces.